An activity model for phase equilibria in the H2O–CO2–NaCl system - Dubacq, B.; Bickle, M.; Evans, Katy (Pergamon-Elsevier Science Ltd, 2013)
We present a semi-empirical thermodynamic model with uncertainties that encompasses the full range of compositions in H2O–CO2–NaCl mixtures in the range of 10–380 °C and 1–3500 bars. For binary H2O–CO2 mixtures, the activity–composition model is built from solubility experiments. The parameters describing interactions between H2O and CO2 are independent of the absolute thermodynamic properties of the end-members and vary strongly non-linearly with pressure and temperature. The activity of water remains higher than 0.88 in CO2-saturated solutions across the entire pressure–temperature range. In the H2O–NaCl system, it is shown that the speciation of aqueous components can be accounted for by a thermodynamic formalism where activities are described by interaction parameters varying with intensive properties such as pressure and temperature but not with concentration or ionic strength, ensuring consistency with the Gibbs–Duhem relation.The thermodynamic model reproduces solubility experiments of halite up to 650 °C and 10 kbar, and accounts for ion pairing of aqueous sodium and chloride ions with the use of associated and dissociated aqueous sodium chloride end-members whose relative proportions vary with salinity. In the H2O–CO2–NaCl system, an activity–composition model reproduces the salting-out effect with interactions parameters between aqueous CO2 and the aqueous species created by halite dissolution. The proposed thermodynamic properties are compatible with the THERMOCALC database (Holland and Powell, 2011) and the equations used to retrieve the activity model in H2O–CO2 can be readily applied to other systems, including minerals.